PHENYLDIBENZOFURANS AND PHENYLDIBENZOTHIOPHENES IN MARINE SEDIMENTARY ROCKS AND HYDROTHERMAL PETROLEUM - Marynowski L.; Rospondek M.J.; Zu Reckendorf R.M.; Simoneit B.R.T. (My University, 2002)
The phenyl derivatives of dibenzo[b,d ]furan and dibenzo[b,d ]thiophene, so far not reported in geological samples, have now been identified in some sedimentary rocks, bitumen and hydrothermal petroleum through a comparison of their retention times and mass spectra with those of authentic standards. All four possible positional isomers were detected for each phenyldibenzo[b,d ]furan (PhDBF) and phenydibenzo[b,d ]thiophene (PhDBT). Their elution sequence is 1-, 4-, 2-and 3-phenyldibenzo[b,d ]furan and 1-, 4-, 2-and 3-phenyldibenzo[b,d ]thiophene on apolar sta-tionary phases. In contrast to phenyldibenzofurans, the distributions of the thiophene series is controlled mainly by the organic matter maturity. In the most mature samples 4-, 2-and 3-PhDBTs prevail over 1-PhDBT, while less mature samples contain mainly 4-PhDBT or 1-PhDBT and 2-, 3-PhDBTs occur at comparable concentrations. However, in samples of low maturity, in addition to the phenyldibenzo[b,d ]thiophene C 18 H 12 S series, other structural isomers of C 18 H 12 S possessing very similar mass spectra were detected. These are likely to be either naphthylbenzo[b]thiophenes and/or phenylnaphtho[b]thiophenes. PhDBFs and PhDBTs are likely to be intermediate products in the formation of more condensed heterocyclic polycyclic aromatic compounds like triphenyleno[1,12Àbcd ]thiophene and tri-phenyleno[1,12-bcd ]furan, and benzobisbenzofurans and benzobisbenzothiophenes, which are commonly detected in geological samples.